Value-Based Intermediation in Islamic Finance in Malaysia: An Overview on Strategy, Issues and Challenges - Mohd Yunus, Saidatolakma; Rizal, Fitra (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study looks into how Value-Based Intermediation (VBI) is framed and implemented in the context of Islamic finance in Malaysia, especially through the efforts of Bank Negara Malaysia (BNM). VBI, which was introduced by BNM in 2017, is an initiative that aims to bring Islamic banking back to its original ethical foundations. It focuses on achieving the higher objectives of Shariah (Maqasid al-Shariah) by promoting practices that generate real, positive impact on the economy, society, and environment without sacrificing financial performance. Research Methods: The research uses qualitative methods, mainly by analysing documents such as the VBI strategy paper and other related guidelines issued by BNM. Results: The study identifies the VBIAF and VBI Scorecard as key instruments that support the integration of value-based principles in Islamic financial institutions. Despite this progress, challenges remain, particularly in shifting the industry’s profit-oriented mindset. The findings also confirm that VBI aligns closely with Maqasid al-Shariah and the United Nations Sustainable Development Goals (SDGs). Conclusion: The study highlights VBI’s potential to transform Malaysia’s Islamic finance landscape toward a more sustainable, value-driven, and impactful system.